Preferred strategies by Australian and VietNamese parents in encouraging their children = Những cách thức động viên con cái của cha mẹ người Úc và Việt Nam - Nguyễn, Thị Quỳnh (2020)
Encouragement plays an important role in life. Encouraged people can be stronger and more confident to overcome their difficulties, more courageous to face their challenges and more determined to continue their good doings. For children, the importance of encouragement is reinforced as Dreikurs (1971) states “a child needs encouragement as a plant need water”. Parents in different cultures have differences in encouraging their children; therefore, an investigation into how parents motivate their children is necessary to discover the effectiveness of this powerful tool of parenting in nurturing and educating children. The study aims to explore verbal encouraging strategies employed by Australian and Vietnamese parents. Subsequently, the similarities and the differences in the choice of verbal encouraging strategies of both groups of participants are found out. Also, some cultural factors leading these differences are in discussion in order to provide readers with a critical look in the causes of the differences, and thus, to diminish the level of the cultural shock when real intercultural communication takes place. Data for the study are collected by means of questionnaires with the participation of 60 parents (30 Australian and 30 Vietnamese parents) and informal interviews. The study realizes eleven verbal encouraging strategies including Comforting/Reassuring, Giving advice, Expressing sympathy, Offering help, Praising, Giving examples, Predicting bright future, Expressing positive emotions, Expressing negative emotions, Requesting and Threatening. The similarities and the differences in the frequency or the preference of strategies are found out and discussed in details. Hence, this paper is expected to serve as a useful reference for further cross-cultural studies.